L2 development during a short English course : Studying Finnish university students’ written syntactic complexity - Mäkynen, Iida (My University, 2023)
This thesis examines Finnish university students’ written syntactic complexity development during a short English course. To examine how students develop in syntactic complexity during a relatively short period of time, two essays of 54 students were examined. The first essay was written in the beginning and the second essay at the end of the course. These two essays were compared to gain a better understanding of how the students’ written syntactic complexity changed. The second aim of the thesis was to determine how learners’ initial syntactic complexity level affects their development. In other words, it was studied whether the syntactic complexity level in the beginning of the course had any positive or negative effects on the learners’ syntactic complexity development. A computational syntactic complexity analysis tool, L2SCA, was utilized to automatically calculate values of ten syntactic complexity indices. For example, mean lengths of different segmentation units, amount of coordination and number of dependent clauses were examined. Furthermore, ten students were chosen to be examined in more detail to answer the second research question. The development of learners with the highest and lowest syntactic complexity values in their first essays were compared. Only three out of the ten indices chosen to measure syntactic complexity showed significant change between the students’ two essays. The students began to write fewer coordinate phrases per clause, coordinate phrases per T-unit and verb phrases per T-unit, meaning that in the second essay, the learners depended less on coordination and did not use as many verb phrases. However, the majority of the indices did not show significant change, suggesting that perhaps the course was not long or intensive enough for the students to show more development in terms of written syntactic complexity. The second aim of the thesis was to get more knowledge on the effect of initial syntactic complexity level. It was found out that learners with lower initial syntactic complexity level showed slightly more development. The difference between the two initial syntactic complexity level groups was, however, only subtle.
Keywords: Complexity, syntactic complexity, L2 development